2005
DOI: 10.1038/sj.bjp.0706222
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the relaxation response induced by bradykinin in the epithelium‐intact guinea‐pig trachea in vitro

Abstract: 1 In this study, we investigated some of the signalling pathways involved in bradykinin (BK)-induced relaxation in epithelium-intact strips of the guinea-pig trachea (GPT þ E). BK induced timeand concentration-dependent relaxation of GPT þ E. Similar responses were observed for prostaglandin E 2 (PGE 2 ) or the combination of subthreshold concentrations of BK plus PGE 2 . 2 The nonselective cyclooxygenase (COX) inhibitors indomethacin or pyroxicam, or the selective COX-2 inhibitors DFU, NS 398 or rofecoxib, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Although various authors reported the absence of COX-2 expression in the tracheobronchial system of normal guinea pigs (Amann et al, 2001;Oguma et al, 2002), the role of COX-2 has been proposed to be relevant in the regulation of tracheal intrinsic tone in this species (Charette et al, 1995), and a constitutive COX-2 expression has been reported in normal airways (Schlemper et al, 2005). Our results from normal guinea pigs, showing that DFU enhances histamineinduced contraction, indicate a functional role for COX-2 isoform that seems to mediate an inhibitory control on airway muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Although various authors reported the absence of COX-2 expression in the tracheobronchial system of normal guinea pigs (Amann et al, 2001;Oguma et al, 2002), the role of COX-2 has been proposed to be relevant in the regulation of tracheal intrinsic tone in this species (Charette et al, 1995), and a constitutive COX-2 expression has been reported in normal airways (Schlemper et al, 2005). Our results from normal guinea pigs, showing that DFU enhances histamineinduced contraction, indicate a functional role for COX-2 isoform that seems to mediate an inhibitory control on airway muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions: Insulin has acute contractile effects on guinea pig airways, which were significantly inhibited by prostaglandin synthesis inhibitor indomethacin confirming the involvement of contractile prostaglandins in insulin-induced airwayinflammatory drug, which inhibits cyclooxygenase enzyme that participate in prostaglandin synthesis from arachidonic acid. 7 It is well-established from the review of literature that insulin-induced isolated tracheal muscle contraction in guinea pig model described in the present study closely resembles the bronchoconstriction induced by pulmonary delivery of inhaled insulin as high concentration of insulin gets deposited in airway smooth muscle compartment in both cases. 8 Aim of our study was to explore the magnitude of insulin-induced airway hyper-reactivity and to evaluate the potential role of prostaglandins in insulin-mediated tracheal tissue contraction of guinea pig in vitro.…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, these data demonstrate that not only M 3 muscarinic but also bradykinin receptors cause bladder contraction in a largely PLC-independent manner. Of note, the recent data on PLCinvolvement in P2Y6 receptor-mediated bladder contraction relied on a high concentration of U 73,122 (50 mM) and did not include a negative control (Yu et al, 2013).Work in guinea pig trachea also supports the idea that bradykinin-induced smooth muscle contraction may occur independently of PLC (Schlemper et al, 2005). Therefore, additional experiments were designed to explore which other signaling pathways may be involved in bradykinin-induced bladder contraction.…”
Section: Fig 4 Bradykinin-induced Bladder Contraction (Top) Effectmentioning
confidence: 95%